(untitled) (Physical Education, Health and Social Sciences, 2025)
Almost every living thing is made of water. It is essential to the existence of life. It is employed in every aspect of both personal and professional life. Untreated ground water is exclusively used for drinking. Since water makes up more than 65% of the mass of an adult human, water is important to human health as it maintains the body’s temperature, getting rid of wastes, and providing the cells with nutrients. Worldwide, water shortages and pollution are major issues. Pakistan, in particular, suffers from a chronic shortage of safe drinking water, in urban and rural areas. The present study was conducted in District Narowal, Punjab, Pakistan. Water samples were collected from the Water Testing Laboratory of District Narowal in 2022. Water quality parameters such as pH, Turbidity, Alkalinity, TDS, Chlorine, Sulphates, Calcium, Magnesium, Hardness, Nitrites, Sodium, Potassium, Fluoride, Iron, and Arsenic were assessed from 1 to 5 according to their significance in the water quality to calculate the Water Quality Index (WQI). Health risk assessment (HRA) was used to calculate the chronic daily intake (CDI) and hazardous quotient (HQ) for each parameter. Using an Excel sheet, a correlation matrix analysis was conducted on 16 water quality metrics and the Water Quality Index (WQI) for water samples, as seeing the degree of linear relationship (R) between variables. ARC GIS 10.5 was employed for spatial analysis, utilizing techniques like Kriging and IDW to enhance accuracy in predicting water quality across the study area. The Correlation Matrix analysis was used to authorize Principle Component Analysis (PCA). A total of 1188 water samples indicated that the Water Quality Index (WQI) at Narowal was approximately 74. The acceptable water of district Narowal was 90% for drinking purposes. Comparison between the mean concentrations showed the Carcinogenic risk. The results indicated that children are at higher risk due to arsenic concentration dissolved in water at District Narowal. To provide a Drinking Water Quality Index (DWQI) for thorough water quality monitoring, this study attempts to evaluate the physicochemical properties of drinking water in District Narowal, Punjab, Pakistan. To identify possible pollutants and their effects on public health, a health risk assessment (HRA) was carried out. Priority areas for water quality improvement are determined.